2014
DOI: 10.1038/ncomms6624
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-engaged TCR is triggered by Lck not associated with CD8 coreceptor

Abstract: The earliest molecular events in T cell recognition have not yet been fully described, and the initial T cell receptor (TCR) triggering mechanism remains a subject of controversy. Here, using TIRF/FRET microscopy, we observe a two-stage interaction between TCR, CD8, and MHCp. There is an early (within seconds) interaction between CD3ζ and the coreceptor CD8 that is independent of the binding of CD8 to MHC, but that requires CD8 association with Lck. Later (several minutes) CD3ζ-CD8 interactions require CD8-MHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
77
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 51 publications
(92 reference statements)
10
77
0
1
Order By: Relevance
“…Interestingly, although we found that pZap70 and pLat had a large fraction of molecules colocalized with CD3ζ, relatively few Lck molecules colocalized with CD3ζ (Fig. 4C), suggesting that transient Lck-CD3ζ interactions may be sufficient to initiate signaling at TCR signaling "hot spots" (26,38). More CD3ζ molecules colocalized with Lck at 5 min than at later time points (Fig.…”
Section: Tcr Engagement Leads To Receptor Clustering Independently Ofmentioning
confidence: 89%
“…Interestingly, although we found that pZap70 and pLat had a large fraction of molecules colocalized with CD3ζ, relatively few Lck molecules colocalized with CD3ζ (Fig. 4C), suggesting that transient Lck-CD3ζ interactions may be sufficient to initiate signaling at TCR signaling "hot spots" (26,38). More CD3ζ molecules colocalized with Lck at 5 min than at later time points (Fig.…”
Section: Tcr Engagement Leads To Receptor Clustering Independently Ofmentioning
confidence: 89%
“…The P a curve measured over a range of t c exhibits a two-stage pattern (Fig. 2C, red), similar to those observed in the studies of TCR/CD8 crosstalk [18][19][20] . Like the previous studies, this two-stage curve cannot be obtained by superposition of two single-stage curves each measured using the same batch of T cells contacted by RBCs coated with only one ligand species (Fig.…”
supporting
confidence: 61%
“…Interactions of two ligands (IgG1 and IgG2) to a common receptor (Fcγ receptor III B, FcγRIIIB) 16 or of two receptors (FcγRIIA and FcγRIIIB) to a common ligand (total IgG) 17 have been found to be concurrent and independent when the bond numbers are low enough for competition to be neglected, resulting in a total bond number that is equal to the sum of two bond species. By comparison, binding of a divalent ligand, pMHC or Thy-1, to the corresponding dual receptors, T cell receptor (TCR) and coreceptor CD8 [18][19][20] or integrin α 5 β 1 and Sydecan-4 21 , is cooperative and synergistic, resulting in an additional trimolecular bond species of greater number and longer duration than the sum of two bimolecular bond species separately formed between the ligand and the two receptors. Interestingly, the formation of the (TCR/CD8)-pMHC trimolecular bond exhibits a time delay and requires intracellular signaling via Src family kinases [18][19][20] whereas that of the (α 5 β 1 /Sydecan-4)-Thy-1 bond is elicited by pulling forces 21 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We further analyzed the spatial colocalization between tension, TCR, CD8 (coreceptor), and lymphocyte-specific kinase (Lck), which is essential for T-cell activation (29,30). In contrast to the tension signal near the cell edge, TCRs were distributed uniformly across the cell-substrate interface (Fig.…”
Section: Tcr-ligand Tension Requires Coreceptor Engagement and Is Modmentioning
confidence: 99%